Studi Kerusakan Jalan Piyungan - Wonosari dari Aspek Geoteknik - Agus Darmawan Adi (Faculty of Engineering, Universitas Gadjah Mada, 2006)
Some road sections in Yogtakarta sufer from frequent damage following the rainy season. Repairs have been conducted regularly and various efforts to improve the road condition have also been done, however, this probletn always comes every year. Soil condition below the road pavement is suspected to give a major contribution on road damage in this region.A series of investigation was carried out on the soil beneath the road of Piyungan-Wonosari section. Field observation on road damage condition was conducted and it was followed by in situ tests, consisting of hand boring, sampling and cone penetration test. Properties of soil were obtained from several laboratory tests. To simulate effect of water changes on soil strength, a series of shear strength tests were performed on the samples made of soil with various water contents.The results indicate that the road damages in this region are resulted by several reasons. At road section built on slope, the damage was mainly caused by downward movement of the Jill which was not rnassive enough standing on the original slope. Soil softening due to water changes is identified to give a major contribution on this problem, especially for road constructed on clays. Expansive soil was also found at some road section. This soil type produces signiJicant amount of pressure and volume changes which lead to movement of the adjacent structures.Keywords : road-damage, soil, strength, water, soften